The effects of therapeutic activity kits in emergency department patients with dementia: Study protocol for a pragmatic randomized control trial. (29th March 2020) - Higgs, Leonie; Atkinson, Diane; Brown, Nathan J.; Schnitker, Linda; Lock, Caitlin; Merlo, Gregory; Kramer, David; Bennett, Leanne; Hughes, James A.
Abstract: Aim: To determine the effectiveness of therapeutic activity kits on health service use and treatment delivered in the emergency department (ED) in patients with pre‐morbid dementia. Design: Pragmatic randomized control trial with equal parallel groups. Methods: Participants with dementia will be randomly assigned to the control group ( N = 56) or the intervention group ( N = 56). The intervention group will be given access to a therapeutic activity kit containing several different activities and sensory stimuli to engage the person with dementia during their ED stay in addition to usual care, and the control group will be given usual care only. A research nurse will observe participants at 30–60‐min intervals throughout their ED stay for responsive behaviours, one‐on‐one nursing, and the use of chemical and physical restraint. This study has received Research Ethics Committee approval from the institutional review board and funding from the Rosemary Bryant Foundation (May 2019). Discussion: Emergency departments are busy and noisy environments and can be intimidating and disorientating for patients with dementia, which can result in responsive behaviours. Responsive behaviours are often managed with restrictive interventions, such as chemical or physical restraint, or with constant bedside nursing (one‐on‐one nursing) to ensure patient safety. Alternatively, non‐restrictive and non‐pharmacological interventions that divert or occupy the attention of patients such as those contained in the therapeutic activity kit can be considered as a more person‐centred strategy. Therapeutic activity kits have been reported as feasible for the use in ED; however, there is limited quality evidence at present to support the implementation of such interventions in the ED. Impact: If this study is successful, it will demonstrate that a therapeutic activity kit containing activities (puzzles, colouring, music, and tactile activities) is inexpensive, easily implemented intervention that can prevent this patient group from demonstrating unsafe behaviours and requiring one‐on‐one nursing and restraints. Abstract : 目的: 探讨治疗活动方案对急诊科(ED)病前痴呆患者的保健服务应用和治疗的有效性。 设计: 实用性随机对照试验(人数相等的平行组)。 方法: 患有痴呆症的受试者将随机分为对照组(N=56)和干预组(N=56)。将向干预组分配一个包含多种不同活动和感官刺激的治疗活动方案, 使患有痴呆症的患者在急诊住院期间, 除常规护理外, 还可接受其他不同活动和感官刺激治疗, 而对照组将只接受常规护理。临床科研护士将在受试者的整个急诊住院期间每隔30 60分钟观察他们的反应性行为, 提供一对一护理, 以及使用化学和物理约束。本研究已从机构审查委员会获得研究伦理委员会批准, 并获得Rosemary Bryant基金会的资助(2019年5月)。 讨论: 急诊科工作繁忙, 环境嘈杂, 如果痴呆症患者身处这一环境中, 可能会感到害怕和不知所措, 从而引发反应性行为。反应性行为通常通过限制性干预措施进行管理, 如化学或物理约束, 或通过持续式床旁护理(一对一护理)来确保患者安全。或者, 采取可转移或占据患者注意力的非限制性和非药理学干预措施, 例如治疗活动方案中包含的干预措施(这类措施被视为是一种更以人为本的策略)。 据称, 治疗活动方案在急诊科中是行之有效的;但目前有关急诊科实施此类干预措施的辅证性质量证据有限。 影响: 如果本研究成功, 将证明包含一系列活动(智力游戏、彩绘、音乐和触觉活动)的治疗活动方案是一种具有成本效益且易于实施的干预措施, 可以防止这类患者群体表现出不安全行为, 并需要一对一的护理和约束。